CONSUMER ATTITUDES TOWARDS ECO-FRIENDLY PRODUCTS: “A COMPREHENSIVE LITERATURE REVIEW" (International Journal of Food and Nutritional Sciences, 2022)
This research paper aims to conduct an in-depth literature review on consumer attitudes towards eco-friendly. As environmental concerns continue to rise, understanding consumer preferences and behaviors related to eco-friendly products has become crucial for businesses and policymakers alike. The paper will explore various aspects of consumer attitudes, perceptions, motivations, and behaviors concerning eco-friendly products, drawing insights from existing literature. By synthesizing and analyzing the current body of knowledge, this paper intends to provide valuable insights for businesses, marketers, and policymakers to effectively promote eco-friendly products and encourage sustainable consumption patterns.